Multi-domain Boundary Element Method in Nonlinear Liquid Sloshing Analysis for Fuel Tanks - Strelnikova, Elena A.; Naumemko, Vitaly V.; Gnitko, Vasyl I. (NTU "KhPI", 2016)
The boundary element method is used for analysis of the non-linear sloshing response of liquid in cylindrical baffled and un-baffled fuel tanks. The liquid is supposed to be an ideal and incompressible one and its flow introduced by the vibrations of a shell is irrotational. The potential formulation is considered for the liquid domain. In this paper the free vibration analysis of the liquid sloshing in the cylindrical shell is carried out in non-linear statement. The non-linear Cauchy-Lagrange integral is involved in the problem statement and the boundary conditions were assigned on the free surface changing in time. Here we use reduced boundary element method. The problem was solved using the single-domain and multi-domain reduced boundary element methods. The fourth-order Runge-Kutta method is employed to advance the solution in the time domain. The rigid baffled tanks with different annular orifices were considered. The time-dependencies of the free surface flood level were obtained numerically for vibrations of the fluid-filled tanks with and without baffles in linear and non-linear statements.
Keywords: nonlinear sloshing; baffles; boundary element method; single and multi-domain approach; singular integral equations